A Rare Case of Medulloblastoma with Supratentorial Metastasis Two Years after Treatment - Reihanian, Zoheir; Behzadnia, Hamid; Namin, Ahmad Kheiri; Zaresharifi, Nooshin (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2020)
One of the most invasive malignant tumors of the cerebellum is medulloblastoma, which is also the most common malignant tumor of the brain in children. Patients with a recurrent disease following initial treatment have the most unfavorable prognosis. The most common metastasis locations are the spine, the posterior fossa, the bones, and the supratentorium. Late medulloblastoma metastasis in the supratentorial intraventricular region is uncommon. We report here a case with supratentorial seeding.
Keywords: medulloblastoma; metastasis; supratentorial; recurrence